Applied Computing and Artificial Intelligence (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Applied computing and artificial intelligence methods have attracted a growing interest in recent years due to their effectiveness at solving technical problems. Recent developments in applied mathematics have largely led to benefits for industrial tasks in different fields, including the aerospace industry, manufacturing, transportation, energy, robotics, materials, informatics, etc. The objective of this Special Issue is to present advanced methods in applied computing and artificial intelligence to address the practical challenges in the related areas. The response of the scientific community has been remarkable, and a large number of papers have been submitted. After a careful peer-review process, 22 high-quality papers have been accepted and published. It is hoped that the papers will have an impact on international scholars in this field and promote further remarkable research in this area.